INFLUENCE OF SEED-TREATMENT BY FUNGICIDES ON BIOMETRICAL FEATURES OF WINTER BARLEY PLANTS - Holiachuk, Ю.; Kosylovych, Г. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Pre-sowing treatment of seed is a necessary element of the system of plant protection against harmful organisms. This protection measure is an important aspect of the modern agrotechnologies focused on full implementation of the genetic potential of a variety. The exterminator’s effect is revealed both in the direct impact on a pest, and in the indirect influence on the biomentical properties of plants that finally results in the increased plant productivity. The influence of the preparation Vibrance Integral 235 FS TH (25 g/l Tebuconazole + 25 g/l Fludioxonil + 175 g/l Tiametoxam + 5 g/l Sedaxane) in rate 2 l/t on biometrical features of the plants of winter barley of Highlight variety was studied. This influence was observed in the end of the phase of the tube and in the earing phase of plants treated with Vibrance Integral 235 FS TH in comparison with the results obtained in control (water treatment of seed). In the variant of the exterminator application in the phase of tube, the features of roots length, plant height and number of leaves on plant were intensified as compared to the control variant. Moreover, the indices of plant height and number of leaves on plant were significantly higher in variant with seed treatment by chemical preparation. In the earing phase one observed uniformity of sowing by the features of ear length and number of spikelets in the ear under seed treatment with Vibrance Integral 235 FS TH. The indices of roots length and ear length of plant were significantly higher. The increased ear length and uniformity of sowing by the features of ear length and number of spikelets in the ear are the main indicators of winter barley productivity. The correlation analysis of the data obtaining at the end of phase of tube confirmed significant rectilinear middle relations between the plant height and leaf width in the control variant and between the leaf width and plant height, and between the leaf width and leaf length in the variant with seed treatment with chemical preparation. The rectilinear strong relations between the plant height and ear length and between the plant height and number of spikelets in the ear, and also between the ear length and number of spikelets in the ear were marked in both variants in the earing phase. A significant inverse middle relation was detected between the plant height and roots length in the variant of seed treatment with chemical preparation.